Increasing Students' Learning Motivation in Science Subjects Using Powerpoint Media at SDN 1 Kuala Pembuang II - Ridwan, Mohamad; Fatchurrahman, M.; Rahmaniati, Rita (International Journal of Universal Education, 2024)
This research aims to determine the increase in learning motivation of students at State Elementary School 1 Kuala Pembuang II which has experienced very significant changes. This research is very rational because it uses a research method of five steps/development phases including; Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations. Data collection techniques in research use test instruments. Data analysis uses quantitative. Learning media is a tool that is considered good in helping convey information, whether in the form of pictures, videos or readings packaged in PowerPoint form so that it can increase student learning motivation in any subject, especially Natural Sciences, to students at Kuala Pembuang II Elementary School. Analysis of the use of PowerPoint as a medium can be seen in two tables of research results which show that students are more happy, enthusiastic, and motivated to focus more on receiving information in Natural Sciences lessons.